Dispensable genome and segmental duplications drive the genome plasticity in Fusarium solani - Abbeah Navasca; Jatinder Singh; Viviana Rivera-Varas; Upinder Gill; Gary Secor; Thomas Baldwin (Frontiers in Fungal Biology)
Fusarium solani is a species complex encompassing a large phylogenetic clade with diverse members occupying varied habitats. We recently reported a unique opportunistic F. solani associated with unusual dark galls in sugarbeet. We assembled the chromosome-level genome of the F. solani sugarbeet isolate strain SB1 using Oxford Nanopore and Hi-C sequencing. The average size of F. solani genomes is 54 Mb, whereas SB1 has a larger genome of 59.38 Mb, organized into 15 chromosomes. The genome expansion of strain SB1 is due to the high repeats and segmental duplications within its three potentially accessory chromosomes. These chromosomes are absent in the closest reference genome with chromosome-level assembly, F. vanettenii 77-13-4. Segmental duplications were found in three chromosomes but are most extensive between two specific SB1 chromosomes, suggesting that this isolate may have doubled its accessory genes. Further comparison of the F. solani strain SB1 genome demonstrates inversions and syntenic regions to an accessory chromosome of F. vanettenii 77-13-4. The pan-genome of 12 publicly available F. solani isolates nearly reached gene saturation, with few new genes discovered after the addition of the last genome. Based on orthogroups and average nucleotide identity, F. solani is not grouped by lifestyle or origin. The pan-genome analysis further revealed the enrichment of several enzymes-coding genes within the dispensable (accessory + unique genes) genome, such as hydrolases, transferases, oxidoreductases, lyases, ligases, isomerase, and dehydrogenase. The evidence presented here suggests that genome plasticity, genetic diversity, and adaptive traits in Fusarium solani are driven by the dispensable genome with significant contributions from segmental duplications.